2016
DOI: 10.1111/jvh.12659
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C viraemia reversibly maintains subset of antigen‐specific T‐bet+ tissue‐like memory B cells

Abstract: Summary Background Chronic antigen exposure and/or ageing increases the frequency of T-box expressed in T cells (T-bet)-expressing B-lymphocytes in mice. The frequency and significance of B-cell T-bet expression during chronic hepatitis C (HCV) infection in human subjects has never been described. Methods Healthy controls, cirrhotic and noncirrhotic HCV-infected patients, and non-HCV patients with cirrhosis were recruited. Peripheral blood mononuclear cells were phenotyped for expression of T-bet and relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 27 publications
6
72
0
Order By: Relevance
“…We also observed involvement of T-bet + B cells in the response to HIV infection, as T-bet was rapidly induced in B cells during the acute phase and T-bet We and others have previously demonstrated an expansion of CD21 -B cell subsets induced by Th1-type human infections, including HIV, malaria, and hepatitis C (30,31,34,35,(60)(61)(62)(63), and expansion of a clonal CD21 -subset has been described during hepatitis B-and hepatitis C-associated mixed cryoglobulinemia (64)(65)(66). Interestingly, maintenance of expanded CD21 -cells in each of these infections appears to be dependent upon pathogen load (34,35,60,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We also observed involvement of T-bet + B cells in the response to HIV infection, as T-bet was rapidly induced in B cells during the acute phase and T-bet We and others have previously demonstrated an expansion of CD21 -B cell subsets induced by Th1-type human infections, including HIV, malaria, and hepatitis C (30,31,34,35,(60)(61)(62)(63), and expansion of a clonal CD21 -subset has been described during hepatitis B-and hepatitis C-associated mixed cryoglobulinemia (64)(65)(66). Interestingly, maintenance of expanded CD21 -cells in each of these infections appears to be dependent upon pathogen load (34,35,60,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, chronic lymphochoriomeningitis (LCMV) viremia is controlled to low levels only in the presence of T-bet + B cells via a chiefly IgG2a-dependent mechanism (6). We previously identified a subset of T-bet-expressing B cells in healthy human blood (26), and B cells expressing either TBX21 transcript or T-bet protein have been described in the context of autoimmune disease, chronic hepatitis C infection, and malaria infection (27)(28)(29)(30)(31), but the biological niche of this population in humans has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…We found that only memory B cells express SASP markers, especially the terminally differentiated B cell subset (CD19+IgD− CD27−), called late-memory/exhausted-memory, tissuelike, or double negative, which of all B cell subsets is the most pro-inflammatory. This subset has been reported to be increased in the blood of healthy elderly individuals 85,90 and in patients with autoimmune 96101 and infectious diseases, 102104 suggesting that, in a favorable inflammatory microenvironment, these cells may expand in vivo in the presence of autoantigens or pathogen-derived antigens, leading to the production of pathogenic (autoimmune) or protective antibodies, respectively.…”
Section: Predictors Of Optimal Vaccine Responsesmentioning
confidence: 99%
“…Recent data suggest that the T-box expressed in T cells (T-bet) transcription factor, critical for inducing sterilizing humoral immunity in acute infections, 6 may also regulate the exhausted state in both autoreactive 7 and antigeninduced anergic B cells. 8,9 No data to date specifically link the anergy properties observed in cryoglobulin-producing B cells and T-bet, but there are phenotypic similarities (CD11c 1 /CD21 low ) that suggest a possible relationship that should be explored; rapid upregulation of T-bet in convalescent CD21 low B cells upon reexposure to autologous HCV strains ex vivo has been observed, 8 suggesting a link between B-cell receptor ligation, T-bet, and the CD21 low exhaustion phenotype.…”
mentioning
confidence: 99%
“…ixed cryoglobulinemia is one of several B-cell proliferative disorders that may result from chronic hepatitis C infection, and it is thought to be driven by expansion of HCV envelope-specific B cells that preferentially use immunoglobulin gene segments V H 1-69 and V k [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]3 and to evolve rheumatoid factor activity through somatic hypermutation.…”
mentioning
confidence: 99%